The effect of perceived usefulness, perceived security, and trust on intention to use in mobile banking with perceived ease of use as a mediation variable - Prawira, Michael Eliezer; Stevianie, Vinnie; Nurcahyo, Rianto (Edelweiss Applied Science and Technology, 2026)
This study examines how Perceived Usefulness, Perceived Security, and Trust impact the intention to use mobile banking, with Perceived Ease of Use acting as a mediating variable. The research targets users of the BCA mobile banking app in Indonesia. This study employs a quantitative cross-sectional survey involving 140 BCA mobile users domiciled in Jakarta and Tangerang through purposive sampling. The analysis used Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that Perceived Usefulness, Perceived Security, and Trust positively affect Perceived Ease of Use. Additionally, Perceived Ease of Use significantly affects the Intention to Use and partially mediates the relationship between the independent variables and the Intention to Use. Perceived Usefulness, Perceived Security, and Trust directly impact the Intention to Use, with Trust and Perceived Security having the strongest influence. The structural model accounts for 47.1% of the variance in Perceived Ease of Use and 70.7% of the variance in the Intention to Use. In summary, the adoption of mobile banking relies on a mix of practical benefits, security assurance, trust in system reliability, and ease of use. These findings offer practical suggestions for banks to boost mobile banking adoption by enhancing security features, fostering user trust, and improving app usability.